Fungsi Pengawasan Dewan Perwakilan Rakyat Daerah dalam Kebijakan Retribusi Perpanjangan Izin Memperkerjakan Tenaga Kerja: Pengawasan, Kebijakan, Tenaga Kerja Asing - fahrizal, Jun; Setiawan, Ramadhani; -, Edison (Jurnal Ilmu Administrasi Negara (JUAN), 2018)
The role of the Regional People's Legislative Assembly (DPRD) as a working partner of the government in the region is needed to control and supervise, which expects that the policy issued does not deviate from the line that has been set. The purpose of this study is to find out the implementation of the supervisory function carried out by the Bintan DPRD towards the DPRD's supervisory function in the Extension Retribution Permit for Employment of Foreign Workers (IMTA/Izin Memperkerjakan Tenaga Kerja Asing) in Bintan Regency, to know the obstacles faced in implementing the supervisory function and what efforts are being taken to overcome obstacles. This study uses qualitative research methods, namely research procedures that produce descriptive data in the form of written or verbal words from people or observed behavior. Data was collected by conducting interviews with several members of the Bintan Regency DPRD, observation, and documentation. Data analysis methods in this study were carried out with the stages of data collection, data reduction, data presentation, and data verification. The results of the study, in the implementation of the supervisory function of the IMTA Extension Retribution Policy in Bintan Regency. The Bintan Regency DPRD always tries to supervise the implementation of the Regional Regulation.